2019
DOI: 10.1093/jas/skz201
|View full text |Cite
|
Sign up to set email alerts
|

Late gestation supplementation of corn dried distiller’s grains plus solubles to beef cows fed a low-quality forage: III. effects on mammary gland blood flow, colostrum and milk production, and calf body weights

Abstract: Objectives were to investigate the effects of supplementation with corn dried distiller’s grains plus solubles (DDGS) to late gestating beef cows on arterial blood flow to the mammary glands during late gestation and early lactation; colostrum and milk production; dystocia and immunity; and calf BW. Cows were fed a control (CON; n = 15; 5.1% CP; 36.2% ADF) diet consisting of 90% corn stover and 10% corn silage on a dry basis offered ad libitum or CON diet with supplementation of DDGS (0.30% of BW; SUP n = 12).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 31 publications
1
27
1
Order By: Relevance
“…Calf intake of IgG from colostrum and serum concentrations of IgG are positively correlated ( Hopkins and Quigley, 1997 ). Maternal prepartum supplementation of protein and energy did not impact the concentration of IgG in the colostrum ( Kennedy et al, 2019 ) and IgG concentration in plasma or serum of the offspring ( Bohnert et al, 2013 ; Kennedy et al, 2019 ; Moriel et al, 2020b ; Palmer et al, 2022a ). Likewise, frequency of protein and energy supplementation did not affect circulating concentrations of IgG in the offspring ( Klein et al, 2014 ; Moriel et al, 2016a ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Calf intake of IgG from colostrum and serum concentrations of IgG are positively correlated ( Hopkins and Quigley, 1997 ). Maternal prepartum supplementation of protein and energy did not impact the concentration of IgG in the colostrum ( Kennedy et al, 2019 ) and IgG concentration in plasma or serum of the offspring ( Bohnert et al, 2013 ; Kennedy et al, 2019 ; Moriel et al, 2020b ; Palmer et al, 2022a ). Likewise, frequency of protein and energy supplementation did not affect circulating concentrations of IgG in the offspring ( Klein et al, 2014 ; Moriel et al, 2016a ).…”
Section: Discussionmentioning
confidence: 94%
“…Prepartum supplementation of protein and energy supplementation increased prepartum BCS of beef cows ( Winterholler et al, 2012 ; Bohnert et al, 2013 ; Kennedy et al, 2019 ; Moriel et al, 2020b ; Palmer et al, 2020 , 2022a , b ; Vedovatto et al, 2022 ), did not impact the percentage of pregnant beef cows in the subsequent breeding season ( Stalker et al, 2007 ; Larson et al, 2009 ; Bohnert et al, 2013 ) but resulted in earlier calving compared to no prepartum supplementation of protein and energy ( Palmer et al, 2020 ). Likewise, prepartum supplementation of DDG at 77 kg/cow from day 0 to 77, regardless of supplementation frequency, was sufficient to prevent or minimize prepartum BCS loss, leading to greater BCS during the first 30 d of the breeding season compared to NOSUP cows.…”
Section: Discussionmentioning
confidence: 98%
“…Distillers' grains are often used as feed ingredients for dairy cows as they have low costs and high protein and amino acid concentrations. It has been shown that the addition of distillers' grains to diets during late pregnancy can substantially increase calf birthweight and that this effect may be related to a considerable increase in uterine horn blood flow velocity and pulsatility index (Kennedy et al, 2019). Increased uterine horn blood flow during pregnancy will increase the foetal absorption of nutrients from the dam.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, calves born to cows fed balanced diet, but fed colostrum from dams fed restricted diets have less serum IgG concentrations at 24 h of life than the calves receiving colostrum from well-nourished cows [ 28 ]. Nutrient-restricted cattle have decreased colostrum tri-iodothyronine concentration which plays an important role on IgG absorption at calf intestinal level [ 29 , 30 ].…”
Section: Dam-foetus Interaction and Ante-natal Developmentmentioning
confidence: 99%